Analysis of Economic Value Added (EVA) Method to Measure Financial Performance at PT. Charoen Pokphand Indonesia, tbk. Case Study 2014 - 2023 - Najla, Aura Nabilat En; Yofi, Yofi (ProBisnis : Jurnal Manajemen, 2025)
This research aims to determine the condition and financial performance of the company for capital suppliers, to control internally, to carry out effective planning and supervision, and as a guideline for improvement efforts and further improvement of the company's performance. Especially in the companies that are being researched, it turns out that they still do not use EVA analysis as an analysis that will be able to determine whether the profits obtained from 2014 to 2023 can create added value to the company or not. The financial data used for this study was taken for six (10) years, from 2014 – 2023. The data of this study was obtained from observation and documentation with NOPAT analysis tools, capital costs, and EVA analysis. The results of this study show that using the EVA (Economic Value Added) method in the research year has been able to provide economic added value for the company, as evidenced by the results of the EVA>0 calculation is of positive value.